Latitudinal patterns of egg size and maternal investment trade‐offs in reef corals. Issue 3 (22nd January 2023) - Gutierrez‐Isaza, Nataly; Sampayo, Eugenia M.; Lovelock, Catherine E.; Dalton, Steven J.; Sims, Carrie A.; Ward, Selina; Pandolfi, John M.
Abstract: Aim: The aims were to test the role of temperature in latitudinal patterns of egg size and investigate maternal investment trade‐offs among coral taxa. Location: Global, from 34° S to 34° N. Time period: 1981–2020. Major taxa studied: Reef coral species from the order Scleractinia. Methods: We compiled a comprehensive geo‐referenced global dataset of egg sizes (diameter or volume) and fecundity (number of eggs per area) for colonial corals (Scleractinia; 123 species, 5359 observations and 39 localities), substantially enhanced by new field collections (>88% of observations). We used Bayesian phylogenetic multilevel models to test for Rass' rule (a hypothesized negative relationship between egg size and temperature); we also included other environmental variables and life history traits. We also tested whether a trade‐off exists between egg size and fecundity in broadcast spawning hermaphroditic corals with horizontal symbiont transmission (HHT). Results: We found a significant relationship between coral egg size and symbiont transmission. Eggs from coral species with vertical symbiont transmission were c . 18.8% smaller than those from species with horizontal symbiont transmission. We also found non‐significant relationships between egg size and sea surface temperature (SST) for broadcast spawning corals and between egg size and fecundity specifically for HHT species. Main conclusions: Contrary to recognized latitudinal patterns of egg size across taxa, our study does not provide support for Rass' rule in corals. Additionally, our findings do not support a maternal investment trade‐off between egg size and fecundity for HHT species. Our study used a phylogenetic framework that should be a standard practice when studying interspecific variation, including investigation of maternal investment and identification of the influence of multiple predictors on larval fitness (egg size), in addition to trade‐offs affecting propagule influx (fecundity). Both these functional traits are vital and have direct consequences for population maintenance and connectivity in sessile organisms, such as corals.